Epithelioid Hemangioendothelioma of Tibia andTalus: A Case Report - Dharmendra Kumar; Vijay K. Jain; Meenakshi Bhardwaj; Ananta K. Naik; Ruchi Nasa; Rajendra K. Arya (Oman Medical Journal, 2015)
Epithelioid hemangioendothelioma (EHE) of the bone is extremely uncommon and consists of less than 1% of primary bone tumors. It is characterized by epithelioid endothelial cells and has variable biological behavior. EHE is more likely to occur between 20 and 30 years of age. Approximately half of EHE present with multifocal disease. Since the behavior of these tumors is intermediate, it is important to not misdiagnose EHE as an angiosarcoma. Here we describe the case of a 43-year-old male who presented with pain and swelling of the leg and ankle to Dr. Ram Manohar Lohia Hospital, India. Radiography and computed tomography of the ankle and leg were performed and suggested an expansile lytic lesion involving the distal tibia and talus bone. The lesion was excised and ankle arthrodesis performed. Histological evaluation of the lesion demonstrated the presence of EHE of the tibia and talus.